Pendaftaran Hak Milik Atas Tanah Melalui Program Pendaftaran Tanah Sistematis Lengkap Oleh Badan Pertanahan Nasional Kabupaten Ende - Hendrikus Haipon (Jayapangus Press, 2021)
The purpose of land registration carried out by the community is to ensure legal certainty as property rights over land owned by every citizen so that if it is claimed by an irresponsible party in the future, it can show the certificate in the government as proof of letter. Land registration carried out by the community is an obligation that must be carried out by all Indonesian citizens who own the land. Land registration has been regulated in the main agrarian law number 5 of 1960 for the sake of legal certainty, which is more clearly regulated in article 19 paragraph (2). Furthermore, the government issued government regulation number 24 of 1997 regarding land registration. The method of registration is carried out in two ways, namely: the first method is systematic, namely the activity of registering land for the first time which is carried out simultaneously which includes all objects of land registration that have not been registered in the territory or part of the territory of a village / kelurahan and the second method is systematic activities. land registration for the first time regarding one or several objects of land registration within the territory or part of a village / kelurahan, individually or in bulk.